Higher Education As An Anti-Corruption Forming Agent - M Faadhilah Suhandi; Denda Ginanjar; Sulistia Agustin (The Eastasouth Journal of Learning and Educations, 2023)
Corruption is currently an ongoing behavior. Even this, Corruption has become a debate and has always been a hot issue in Indonesia. It seems to be a common thing in society, and then concern arises because this incident can be found anywhere in government and educational institutions. Therefore, the government's efforts to enforce and eradicate it continues to be intensively carried out by the government from a legal perspective. But maybe the government has forgotten the fundamental aspects, namely Education; only a little has been implemented through Education, even though Education can be used to eradicate Corruption. Anti-corruption Education is already present at the school level, starting from elementary school, middle school, to university, but all that is theoretical. Not yet are the actions or methods that must be carried out by students and teachers in implementing anti-corruption practices. In this case, it is necessary to have a critical view of Education that encourages teacher-to-student learning to build awareness about how they act against Corruption.